FORMULASI GEL HAND SANITIZER NON ALKOHOL DARI CUKA APEL - Joko Santoso; Susiyarti; Aldi Budi Riyanta (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2022)
Hand sanitizer among the community has a high alcohol content of up to 80% considered not halal products. Whereas according to Muslims related to halal products, alcohol is included in nonhalal products as an alternative to existing alcohol hand sanitizer preparations. So it needs to be made hand sanitizer based on halal and certainly has antibacterial activities. Vinegar is one of the active ingredients that have bacterial activity and has the potential to be made in gel hand sanitizer formulations. The aim of this research is to make a hand sanitizer formulation that meets SNI standards. The hand sanitizer will be made using a vinegar base made from apples with a formula of 5; 7.5 and 10%. This active ingredient formula is made into the gel with the use of other ingredients such as carbopol, TEA, methylparaben, glycerin, and aqua dest. The gel hand sanitizer formula is then conducted physical properties test to obtain SNI standards such as organoleptic test with five senses, pH with stick pH, viscosity, in addition to being tested anti-irritant with skin surface smear method. As for data analysis used one-way anova method with SPSS software. The results showed that the gel hand sanitizer formula of vinegar organoleptic and homogeneity has met the standards in addition to the viscosity of adhesion to irritant test. However, the pH and spread values have not met the standards.